Zooming In: Children as Guides and Informants in Merauke, West Papua 1905-1910 - Reichgelt, Marleen (Culture Unbound, 2023)
At the heart of this article is the presence of Indigenous children in photographs of explorative travels taken by Dutch Missionaries of the Sacred Heart of Jesus in Netherlands New Guinea (present-day West Papua, Indonesia) in the early twentieth century. Departing from the hypothesis that the children may have been guiding the missionaries, this research studies if and how young West Papuans acted as ‘local intermediaries’ in the early years of colonial settlement. ‘Zooming in’ on engagements between missionaries and children in both visual and textual sources, two paradoxical aspects of Indigenous children in missionary archives are grappled with: their centrality as objects of civilising practices on the one hand, and their marginalisation as historical subjects in colonial textual practices on the other. The visual and textual are brought in conversation: the active presence of children as individual historical actors participating in processes of colonisation in the photographs helps to see children and their actions in ‘still’ discourse, to contextualise captured instances in time and space. This shows how and when missionaries depended on the knowledge, skills, and networks of local children to introduce them to their new working ground. This article thus adds to the existing body of literature on colonial intermediaries, in which young people constitute an overlooked group, and to complement understandings of non-elite colonial childhoods of Indigenous children outside of familial or institutional contexts.